The thinking body in social space: philosophical foundations of inclusion in the framework of the cultural-historical approach (based on the works of L.S. Vygotsky and E.V. Ilyenkov) - Bagdasarova, N.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The aim of this study is to analyze how the philosophical ideas of L.S. Vygotsky and E.V. Ilyenkov can be used today to understand and interpret the concept of social inclusion. In his reflections, Ilyenkov relied on Spinoza's ideas that thinking is inseparable from the "thinking body". Although modern discussions of inclusive education more often discuss the concepts of "autonomy", "authenticity" and "embodiment", they paradoxically lack the concept of "subject" which was central to Soviet educational psychology created in the cultural-historical tradition. It can be assumed that the reason for this is an overly rational and intellectualized idea of ​​​​this "subject". This means that if in this tradition we discuss a child with a disability as a subject of pedagogical influence as a "thinking body", there is a risk that the emphasis will again be on the word "thinking" and not on the word "body". A rationalized arrangement of accents will exclude the idea of ​​"affect" in all discussions of a self-determining subject as the goal of pedagogical influence and child development in general. However, if the goal of education, including inclusive education is to imagine Spinoza's "thinking body" acting in the space of other bodies as a subject, then "subject" may turn out to be the concept that will combine autonomy, authenticity and embodiment. From the point of view of the cultural-historical approach the "thinking body" moves among bodies that are according to Ilyenkov (following Marx) are "non-organic bodies of human". This environment consists almost completely of the objects that were made by humans or adjusted by humans for humans' use. On the other hand, the thinking body moves among other "thinking bodies", that is, in the social environment. It is this movement (which simply cannot be divided into two different types of movement in two different environments) that forms the "thinking body" both as a "body", with its affects and physical reactions and as "thinking" with its understanding of the world and attitude towards it. Using this interpretation of human being is possible to come up with additional aspects for conceptualizing "inclusion" Целью данного исследования является анализ того, как философские идеи Л.С. Выготского и Э.В. Ильенкова могут быть использованы сегодня для понимания и интерпретации понятия социальной инклюзии. В своих размышлениях Ильенков опирался на идеи Спинозы о том, что мышление неотделимо от «мыслящего тела». При том, что в современных дискуссиях об инклюзивном образовании чаще обсуждаются понятия «автономности», «аутентичности» и «воплощенности», в них парадоксальным образом отсутствует понятие «субъекта», которое было центральным для советской педагогической психологии, созданной в культурно-исторической традиции. Можно предположить, что причиной этого является слишком рациональное и интеллектуализированное представление об этом «субъекте». Это значит, что, если в данной традиции обсуждать ребенка с инвалидностью как субъекта педагогического воздействия в качестве «мыслящего тела», есть риск, что акцент опять окажется на слове «мыслящее», а не на слове «тело». Рационализированная расстановка акцентов исключит представление об «аффекте» во всех рассуждениях о самоопределяющемся субъекте как цели педагогического воздействия и развития человека в целом. Однако если целью образования, включая инклюзивное образование, представить «мыслящее тело» Спинозы, действующее в пространстве других тел, как субъекта, то «субъект» может оказаться тем понятием, которое соберет в себе и автономность, и аутентичность, и воплощенность. С точки зрения культурно-исторического подхода, «мыслящее тело» движется среди тел, которые являются «неорганическими телами человека», т. е. в среде предметной. С другой стороны, мыслящее тело движется среди других «мыслящих тел», т. е. в среде социальной. Именно это движение, которое, в принципе, невозможно разделить на два разных типа движения в двух различных средах, и формирует «мыслящее тело» и как «тело», с его аффектами и физическими реакциями, и как «мыслящее» с его пониманием мира и отношением к нему. Используя такую интерпретацию человека, можно подойти и к дополнительным возможностям концептуализации понятия «инклюзии».